SOCIAL AND POLITICAL ACTIVITY URP-USRP ON THE POKYTTJA - Міщук, А. І.; Міщук, М. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article is devoted to the research the organization structure of the Ukraine Radical Party – Ukrainian Social-Radical Party, one of the most active in political respect parties in the social-political life of the West Ukraine in 1918-1939 years. On the basis of the archived documents and memoirs, publicist and scientific documents the role of radical party is explored in alteration of state structures of ZUNR (West Ukrainian Public Republic), in realization of idea of cathedral of Ukraine, defense of its independence and social-political activity in the conditions of the Polish occupation mode. It is shown, that radical forces made a political life in the region more active and that all this time they defend the main aim of the nation which was the creation of the Ukrainian sovereign state.